Kearifan Lokal Roko Molas Poco dalam Perspektif Ekologi dan Konservasi Alam (Kajian Etnis Manggarai) - Ekaputra, Paulus Rudirudolof; Ngama, Yulita Erlina; Lidi, Maria Waldetrudis (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study examines the Roko Molas Poco Ritual as a form of local wisdom from an ecological and nature conservation perspective. The purpose of this study is to examine in depth the ecological values in the Roko Molas Poco traditional rite. This tradition is a traditional practice that contains inherited spiritual, social, and ecological values. This study uses a qualitative descriptive approach with data collection techniques through literature studies and interviews with traditional leaders. Data are analyzed through the process of data reduction, data presentation, verification, and drawing conclusions to obtain in-depth and contextual meaning. The results show that at each stage of the Roko Molas Poco contains symbols that depict environmental ethics and traditional conservation efforts, including the selection of the main wood (siri bongkok), the Ela Racang Cola ritual, the carrying of siri bongkok, the Ela Hambor Haju ritual, and the installation of siri bongkok. The Roko Molas Poco ritual has relevance in environmental education and nature conservation, namely in learning environmental values and ethics. This ritual instills the noble values of respect, appreciation, responsibility, and an awareness of human dependence on nature as a source of life. Thus, Roko Molas Poco serves as a preventive and participatory conservation instrument. This study recommends integrating the ecological values of Roko Molas Poco into environmental education curricula and community-based environmental conservation programs.